Perbuatan Melawan Hukum Komisaris terhadap Pemberhentian Sementara Direksi Perseroan Terbatas - Eko Rial Nugroho (Fakultas Hukum Universitas Islam Indonesia, 2013)
The A Limited Liability Company has a company organ which runs the company functions, and the activities of the staff of the organ are not for the interest of themselves but for, on behalf of, and as a form of responsibility of the company as a legal entity. The problems discussed here are: First, is the legal action of the board of commissioners of PT. JOBS DB to temporarily suspend the board of directors of PT. JOBS DB categorized as illegal? Second, what are the legal effects of the action of the board of commissioners of PT. JOBS DB to temporarily suspend the board of directors of PT. JOBS DB which is categorized as illegal? This research aims to find out if the legal action of the board of commissioners of PT. JOBS DB to temporarily suspend the board of directors of PT. JOBS DB is categorized as illegal and the legal effects of the action of the board of commissioners of PT. JOBS DB to temporarily suspend the board of directors of PT. JOBS DB which is categorized as illegal. This research is a normative legal study using qualitative analysis. This research concludes that Sung Samuel Ham Wing as the commissioner of PT. JOBS DB and PT. JOBS DB have violated the provisions regulating the procedures of the termination of the member of the board of directors in both the Laws of Limited Liability Company and the Articles of Establishment of the company, and they have performed the illegal action in accordance to the Article 1365 of Civil Law Code. Therefore, the action of the termination is illegitimate and must never be considered exist.